Effect of Pregabalin and Diclofenac on tactile allodynia, mechanical hyperalgesia and pro inflammatory cytokine levels (IL-6, IL-1β) induced by chronic constriction injury of the infraorbital nerve in rats. (April 2018) - Khan, Junad; Noboru, Noma; Imamura, Yoshiki; Eliav, Eli
Abstract: The present study evaluated the effects of systemic pregabalin (PG) and diclofenac (Dic) on neuropathic orofacial pain induced by chronic constriction injury (CCI) of the infraorbital nerve (ION) and on the pro-inflammatory cytokines levels in the affected nerve. Fifty-four rats underwent left infra orbital nerve CCI, and 7 days after the procedure as the pain developed, the rats were randomly assigned to one of the treatment groups: PG 300, 30 or 10 mg/kg, Dic 10, 5 or 1 mg/kg or saline group (Sal) (n/group = 8). Addiitonal 8 rats served as naïve control group. Tactile-allodynia and Mechano-hyperalgesia were tested before the surgical procedure and at days 7, 8, and 9 postoperatively. On the 9th day, the rats were euthanized and the affected and contralateral sciatic nerves were harvested to assess IL-6 and IL-1β nerve levels employing enzyme linked immunosorbent assay (ELISA). Daily injection of PG (all doses) significantly reduced tactile-allodynia and mechano-hyperalgesia (p < .05) while Dic did not. On the 9th day, the ipsilateral nerve IL-6 levels were significantly decreased (p < .05) in the PG and DIC groups compared to the Sal group. IL-1β levels demonstrated a significant reduction (p < .05) in the PG group when compared to saline. These results suggest that PG but not Dic may be effective in reducing neuropathic orofacial pain. The mechanisms of action may be associated to some extent with reduction in IL-1β levels in the affected nerve.